2011
DOI: 10.1007/s00415-011-6086-x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid/serum gradient of IgG is associated with disability at acute attacks of neuromyelitis optica

Abstract: Increased blood-brain barrier (BBB) disruption can be found in patients with neuromyelitis optica (NMO); however, its clinical implication and association with disability at acute attack remains obscure. The purpose of the study was to evaluate the clinical significance of BBB disruption and the subsequent cerebrospinal fluid (CSF)/serum IgG gradient in NMO. Retrospective analysis was made of acute-stage CSF samples from NMO (n = 40) and multiple sclerosis (MS; n = 26) patients. The CSF/serum IgG gradient (QIg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…NMO IgG is detected in CSF and levels are predicted by recent relapse and high serum NMO IgG titer [26, 43]. Increased total CSF protein and elevated CSF lactate and albumin levels also correlate with NMO disease severity and acute relapse, suggesting a relationship between dysfunction at the blood–CSF barrier and disability [26, 31, 82]. Conversely, in a study of ten NMO patients with CSF NMO IgG measured at relapse, follow-up measurements after treatment revealed that a reduction in NMO IgG in CSF correlated with clinical improvement, though serum levels were not correlated with remission [11].…”
Section: Discussionmentioning
confidence: 99%
“…NMO IgG is detected in CSF and levels are predicted by recent relapse and high serum NMO IgG titer [26, 43]. Increased total CSF protein and elevated CSF lactate and albumin levels also correlate with NMO disease severity and acute relapse, suggesting a relationship between dysfunction at the blood–CSF barrier and disability [26, 31, 82]. Conversely, in a study of ten NMO patients with CSF NMO IgG measured at relapse, follow-up measurements after treatment revealed that a reduction in NMO IgG in CSF correlated with clinical improvement, though serum levels were not correlated with remission [11].…”
Section: Discussionmentioning
confidence: 99%
“…NMO is distinguished from MS by the presence in the serum of a pathogenic autoantibody to aquaporin-4 (AQP4-Ab) [7], by severe optic and spinal attacks [8], and by the presence of a severely disrupted blood–brain barrier [9]. The relative frequency of NMO to that of MS (NMO/MS ratio) was previously reported to be high in Thailand (1.4) [10] and Japan (0.29–0.59) [11,12], compared to that in Europe (0.024) [13] and Latin America (0.073–0.26) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Serum from NMO patients was tested for the presence of AQP4-Ab at the Weatherall Institute of Molecular Medicine (John Radcliffe Hospital, Oxford, UK) using a cell-based assay as described previously [33]. Serum and CSF samples were obtained from NMO patients during the acute stage and before the initiation of steroid pulse treatment [34]. The number of white blood cells (WBC) and levels of protein, glucose, albumin, and IgG were also assessed in the CSF of patients.…”
Section: Methodsmentioning
confidence: 99%
“…Patients who have severe attacks of NMO can experience disruption of the blood brain barrier (BBB) [34]. Considering that some OHCs, such as 27-OHC, can enter into the CNS from the circulation, the disruption of the BBB in severe NMO patients may affect the CSF OHC concentration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation